2000
DOI: 10.1161/01.str.31.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Antioxidant Activity Is Associated With High Lesion Volume and Neurological Impairment in Stroke

Abstract: Background and Purpose-Oxidative stress is probably involved in neuronal damage induced by ischemia-reperfusion.The purpose of this study was to assess the role of antioxidant activity in cerebral ischemic stroke. Methods-Antioxidant activity of blood plasma and cerebrospinal fluid was assessed in 22 patients with cerebral hemisphere infarction that was verified and quantified by MRI. Results-Low total peroxyl radical trapping potential of plasma, but not of cerebrospinal fluid, was associated with high lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 35 publications
(24 reference statements)
8
99
3
1
Order By: Relevance
“…It was shown that concentration of GSH decreases early after ischemia (Cooper et al, 1980;Rehncrona et al, 1980) in rats, plasma concentration of protein thiols is associated with the degree of neurological impairment (Leinonen et al, 2000), ischemic outcome is worsened by pharmacological depletion of GSH (Vanella et al, 1993). Depletion of the total GSH and decrease of GSH/GSSG ratio are markers for oxidative stress in ischemic brain and as long as 72 h may be required to restore concentrations to normal values following an ischemic insult according to (Namba et al,2001;Park et al, 2000).…”
Section: Glutathionementioning
confidence: 99%
“…It was shown that concentration of GSH decreases early after ischemia (Cooper et al, 1980;Rehncrona et al, 1980) in rats, plasma concentration of protein thiols is associated with the degree of neurological impairment (Leinonen et al, 2000), ischemic outcome is worsened by pharmacological depletion of GSH (Vanella et al, 1993). Depletion of the total GSH and decrease of GSH/GSSG ratio are markers for oxidative stress in ischemic brain and as long as 72 h may be required to restore concentrations to normal values following an ischemic insult according to (Namba et al,2001;Park et al, 2000).…”
Section: Glutathionementioning
confidence: 99%
“…A recent uncontrolled study of 22 ischaemic stroke patients reported an association between the plasma concentration of ascorbic acid and a-tocopherol and the degree of neurological impairment after ischaemic stroke (Leinonen et al, 2000). The same study demonstrated an association between plasma total antioxidant activity and the volume of ischaemic cerebral infarction and the degree of subsequent neurological impairment.…”
Section: Discussionmentioning
confidence: 84%
“…There is evidence that free radical production is an important mechanism of brain injury after exposure to ischaemia and reperfusion (Traystman et al, 1991). While it is not possible to make direct measurements of antioxidant activity and oxidant damage in this target tissue, concentrations of antioxidants and products of oxidative damage in plasma have proved informative in other studies of stroke (Cherubini et al, 2000;Leinonen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations